Engineering electronic structure to prolong relaxation times in molecular qubits by minimising orbital angular momentum - Ana-Maria Ariciu (Nature Portfolio, 2019)
Molecular spin qubits show great promise for quantum information processing, but loss of phase information due to noise interference hinders their applicability. Here the authors engineer the electronic configurations of the metal centres in a series of divalent rare-earth complexes and succeed in prolonging their phase memory times.